STRUKTUR POPULASI DAN POTENSI REPRODUKSI INDUK TERNAK KAMBING DI KECAMATAN KESUI WATUBELA KABUPATEN SERAM BAGIAN TIMUR - Rumaratu, Moh. Arsad; Siwa, Isak P.; Labetubun, Jusak (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aims to determine the population structure and reproductive potential of goats in Kesui Watubela District, East Seram Regency. The method used in this study was a survey. The determination of sample villages and respondents used a purposive sampling method. The selected sample villages were Tanah Baru Village, Kulwar Village, Kelbultak Village, ADM Guliar Village, and Tamher Timur Village, with 10 respondents selected from each village. The variables observed in this study consist of General Variables consisting of Age, Education, Occupation, Source and Method of Selecting Seeds, Length of Business and Maintenance System and Special Variables consisting of Population Structure and Reproductive Potential of Goat Breeders including Age of First Mating, Pregnancy Rate, Litter Size, Type of Birth and Pre-Weaning Mortality. The results of the study showed that the structure of the goat livestock population at the research location was dominated by Adult Females 200 heads (27.2%) then successively followed by Young Females 171 heads (26.84%), Young Females 116 heads (15.7%), Young Males 112 heads (15.2%), Young Males 101 heads (13.7%), and Adult Males 89 heads (12.1%) and their reproductive potential was Age of First Mating 9.1 ± 0.8 months; Pregnancy Rate 89.47%; Birth Rate 1.23 / mother / birth; Type of birth: Single birth 76.70% and twins 23.29%; Pre-weaning mortality 8.2%